Formulation and evaluation of intragastric floating drug delivery system of diltiazem hydrochloride - Gattani, Yogesh S; Bhagwat, Durgacharan A; Maske, Akhil P (Asian Journal of Pharmaceutics (AJP), 2014)
The present study is aimed towards formulation and evaluation of floating multiparticulate oral drug delivery system of diltiazem hydrochloride, which can provide sustained release. The work also aims to study various parameters affecting the behavior of floating multiparticulate in oral dosage form. Floating microspheres were prepared by non-aqueous emulsification solvent evaporation technique, using ethyl cellulose and Eudragit RS-100 as the rate controlling polymer.The in vitro performance was evaluated by the usual pharmacopoeial and other tests such as drug-polymer compatibility, (%) yield, particle size analysis, drug entrapment efficiency, surface topography, in vitro floatability and release studies. Results show that the mixing ratio of components in the organic phase affected the size, size distribution (199-320 Î¼m), drug content (59-84%), %yield (57-77%) and drug release of microsphere (45-99% after 12 h) and floating time >12 h. The best results were obtained at the ratio of drug: polymer Eudragit RS-100 (1:3). In most cases, good in vitro floating behavior was observed and broad variety of drug release pattern could be achieved by variation of the polymer ratio, which was optimized to match target release profile. Stability studies showed no significant change in the drug content in the formulation even after 3 months.The data obtained in this study thus suggest that a micro particulate floating dosage form of diltiazem hydrochloride can be successfully designed to give controlled delivery and improved oral bioavailability.